Associations between oxidation balance score and abdominal aortic calcification, and the mediating role of glycohemoglobin: a nationally representative cross-sectional study from NHANES - Liu, Heqian; Wu, Yifei; Liu, Zhenyu; Ren, Hongzhi; Wu, Ya; Liu, Yong (Frontiers in Nutrition, 2025)
BackgroundAbdominal aortic calcification (AAC) is prevalent among middle-aged and elderly populations, elevating the risk of cardiovascular and cerebrovascular events. Leveraging data from the National Health and Nutrition Examination Survey (NHANES), we conducted a nationally representative cross-sectional study. Our aim was to evaluate whether subjective interventions could influence AAC scores by modifying the antioxidant/pro-oxidant status of individuals and to investigate the role of glycohemoglobin in this relationship.MethodsThe study analyzed data from 1,600 U.S. adults. The study used oxidation balance score (OBS) as an exposure variable derived from 16 dietary and 4 lifestyle factors, as well as glycohemoglobin obtained from blood tests. The main outcome measure was AAC, which was evaluated by dual-energy X-ray absorption and quantified by Kauppila scoring system.ResultsThe mean (SD) age of the 1,600 patients was 56.53 (10.90) years, with a female predominance (50.22%). According to weighted linear regressions not adjusted for covariates, the AAC scores were lower in the third and fourth quartile groups of OBS than in the first quartile group of OBS (Q3: coefficients [coef], −0.92 [95% CI, −1.64 to-0.20], p = 0.017; Q4: coefficients [coef], −0.97 [95% CI, −1.86 ~ −0.08; p < 0.035]). According to the weighted linear regression subgroup analyses, there were no significant OBS-AAC correlations among males (p > 0.05), but there were significant correlations among females (p < 0.05). Smooth fitting curves showed a more significant trend of change in the negative correlation between OBS and AAC scores in postmenopausal women than in premenopausal women. In further mediation analyses, glycohemoglobin was identified as a mediator of the relationship between the oxidative balance score and AAC.ConclusionThis study revealed a significant negative correlation between OBS and AAC scores, particularly in postmenopausal women. The negative correlation between OBS and AAC is partly mediated by glycohemoglobin.